1998
DOI: 10.1002/(sici)1097-0274(199806)33:6<537::aid-ajim3>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Occupation and the risk of laryngeal cancer in Uruguay

Abstract: In a case‐control analysis involving 112 patients afflicted by laryngeal cancer and 509 controls diagnosed with cancers not related to tobacco and alcohol exposures, we studied the effects of type of employment and of substances present in the workplace on laryngeal cancer risk. Effects were measured relative to those never employed or never exposed to the substances. All analyses were controlled for age, tobacco smoking, and alcohol drinking through unconditional logistic regression and stratified analysis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 16 publications
1
24
2
9
Order By: Relevance
“…Some authors have suggested that the risk of laryngeal cancer associated with asbestos exposure might be higher among smokers [Smith et al, 1990;De Stefani et al, 1998]. Our study does not support this suggestion: we found no signi®cant interaction between smoking and asbestos in our analyses, for any of the anatomic sites studied.…”
Section: Asbestoscontrasting
confidence: 97%
See 1 more Smart Citation
“…Some authors have suggested that the risk of laryngeal cancer associated with asbestos exposure might be higher among smokers [Smith et al, 1990;De Stefani et al, 1998]. Our study does not support this suggestion: we found no signi®cant interaction between smoking and asbestos in our analyses, for any of the anatomic sites studied.…”
Section: Asbestoscontrasting
confidence: 97%
“…Some cohort studies have reported an elevated SMR (or SIR) of laryngeal cancer in populations of workers highly exposed to asbestos [Newhouse et al, 1985;Raffn et al, 1989;Piolatto et al, 1990], but their resultsÐwhich do not take smoking or drinking into accountÐmust be put into perspective, especially insofar as other cohort studies in the asbestos industry have not reported signi®cant results [McDonald et al, 1980;Berry et al, 1983;Gardner et al, 1986;Enterline et al, 1987;Hughes et al, 1987;Armstrong et al, 1988;Tsai et al, 1996] or have not observed deaths from laryngeal cancer [Thomas et al, 1982;McDonald et al, 1983]. In contrast, several case-control studies that included an adjustment for smoking level [Zheng et al, 1992] or smoking and drinking levels [Olsen et al, 1984;De Stefani et al, 1998;Gustavsson et al, 1998] have reported signi®cant associations between laryngeal cancer and asbestos exposure, with odds ratios close to 2. We did not observe this signi®cant association in our study, nor did several other case-control studies [Hinds et al, 1979;Zagraniski et al, 1986;Ahrens et al, 1991;Wortley et al, 1992;Muscat et al, 1992;Imbernon et al, 1995].…”
Section: Asbestosmentioning
confidence: 99%
“…The risk of laryngeal cancer associated with asbestos exposure might be higher among smokers. 42 Another way to put this is that the observed female cases of laryngeal cancer in included studies were too small to detect this association due to lower statistical power.…”
Section: Discussionmentioning
confidence: 97%
“…Findings linking an increased risk of laryngeal cancer to asbestos exposure are contrasting, some studies reporting a positive association [Shettigara and Morgan, 1975;Brown et al, 1988;Tola et al, 1988;Smith et al, 1990;De Stefani et al, 1998], and others showing negative [Chan and Gee, 1988] or inconclusive [Finkelstein, 1989] correlations. Mortality from laryngeal cancer is 10 times lower than that from lung cancer in the general population in Italy [Verdecchia et al, 1997] and more than 50% of the incident cases survive for at least 10 years after diagnosis.…”
Section: Discussionmentioning
confidence: 99%